Influence of Independent Board Commissioner, Institutional Ownership, and Audit Committee on Tax Avoidance: Pengaruh Independent Board Commissioner, Institutional Ownership, Dan Audit Committee Terhadap Tax Avoidance - Khoiriyah Ma'rufah; Santi Rahma Dewi (Academia Open, 2021)
This study aims to determine the effect of the Independent Board Commissioner, Institutional Ownership and Audit Committee on Tax Avoidance. This study uses quantitative research methods using statistical techniques by processing existing data to prove the proposed research hypothesis. In this case, the object of research is a mining company listed on the Indonesia Stock Exchange during the 2015-2019 period. Purposive sampling method for determining the sample with a population of 39 companies and a sample of 11 companies. The analytical method used is multiple regression analysis with SPSS version 25 program. Partially, the results show that the independent board commissioner and audit committee have no effect on tax avoidance. Meanwhile, institutional ownership has an effect on tax avoidance.